From Indigenous Knowledge to Human Security: A Case Study of Sekolah Adat Kewang in Maluku, Indonesia - Tri Fatharini, Anjani; Aini, Aulia Nur; Anggraheni, Palupi (Global Local Interactions: Journal of International Relations, 2024)
A prevalent narrative posits that the rights of indigenous peoples are often jeopardized by state interests due to an imbalance of power. The protection of local knowledge and customary law is closely linked with the need to address external threats. The Negeri Haruku indigenous peoples, sensitive to global environmental concerns, particularly climate change, recognize the importance of harmonizing human-nature relations through traditional practices passed down through generations. This article explores how the indigenous people of Negeri Haruku contribute to environmental conservation through their indigenous knowledge and how efforts to preserve this knowledge via the establishment of Sekolah Adat Kewang enhance human security. Data was collected from both primary and secondary sources, including interviews, journal articles, books, reports, and websites. Using the concepts of indigenous knowledge and human security, this article demonstrates that the local knowledge of the Negeri Haruku indigenous people has been preserved for future generations through Sekolah Adat Kewang. This institution not only preserves ancestral values but also serves as an educational platform to ensure the environmental security of the Negeri Haruku community. The concept of environmental security is implemented through customary environmental protection measures based on the principles of Sasi (customary law). These measures encompass various types of Sasi, including Sea Sasi, Forest Sasi, River Sasi, and Inland Sasi.